USING OF THE CARE SCALE IN MONITORING THE TREATMENT OF ACUTE CORONAVIRUS PNEUMONIA - Oktyabr R. Teshaev,; Gulbahor E. Rakhmonova , (Central Asian Journal of Medicine, 2025)
The mechanisms of pneumonia caused by SARS-CoV-2 appear particularly complex. In some cases, a reaction called a "cytokine storm" occurs. The effect is extensive tissue damage with dysfunctional coagulation and inflammatory response, as well as pulmonary microvascular thrombosis associated with viral lung injury. Chest X-ray is not recommended as a first-line imaging method for COVID-19 diagnosis due to its limited sensitivity in detecting opaque glass and other early pulmonary signs of infection. He demonstrated high sensitivity, but limited individuality. The changes observed on chest X-rays of patients with COVID-19 are similar to changes on CT, and both methods usually show bilateral peripheral consolidation and opacity in the form of a dull mirror. It has been established that the severity of abnormalities on chest X-rays peaks 10-12 days after the onset of symptoms. Chest X-ray shows better results in monitoring of treatment in COVID-19 with good sensitivity (85%) and diagnostic accuracy.